The Effect of Ease of Use and Service Quality on Customer Loyalty With Satisfaction as an Intervening Variable - Sarintan Abdul Kadir; Ratna Roostika (Jurnal Indonesia Sosial Teknologi, 2024)
This research examines the effect of ease of use and service quality on customer loyalty, with satisfaction as an intervening variable using mobile banking applications in Indonesia. The method used is quantitative descriptive with a purposive sampling technique. The sample for this research was 210 respondents. The data analysis method uses structural equation modelling SEM (Structural Equation Modeling) assisted by the AMOS version 25 and SPSS version 26 programs. This research shows that ease of use and service quality influence customer loyalty, ease of use and service quality influence satisfaction, and Satisfaction influences customer loyalty. Based on the research and data analysis results, it can be concluded that the ease of use and quality of m-banking services in Indonesia positively and significantly affect customer satisfaction, increasing customer loyalty to using m-banking applications.